Microfluidic platform with four orthogonal and overlapping gradients for soluble compound screening in regenerative medicine research. Issue 3 (12th November 2014) - Harink, Björn; Le Gac, Séverine; Barata, David; van Blitterswijk, Clemens; Habibovic, Pamela; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> We present here a screening method based on a microfluidic platform, which can generate four orthogonal and overlapping concentration gradients of soluble compounds over a monolayer of cells, in combination with automated and in situ image analysis, for use in regenerative medicine research. The device includes a square chamber in which cells are grown, and four independent supply channels along the sides of the chamber, which are connected through an array of small diffusion channels. Compounds flown through the supply channels diffuse through diffusion channels into the chamber to create a gradient over the cell culture area. Further, the chamber is connected to two channels intended for introduction of cells and in situ staining. In this study, the dimensions of the different channels were optimized through finite element modeling to yield stable gradients, and two designs were used with gradients spanning 2.9–2.4 μM and 3.4–2.0 μM. Next, overlapping gradients were generated using four rhodamine‐derived fluorescent dyes, and imaged using confocal microscopy. Finally, the platform was applied to assess the concentration‐dependent response of an osteoblastic cell line exposed to a hypoxia‐mimicking molecule phenanthroline, using an in situ fluorescent staining assay in combination with image analysis, applicable to closed microfluidic devices. The on‐chip assay yielded results comparable to those observed in conventional culture, where a range of concentrations was tested in independent microwells. In the future, we intend to use this method to complement or replace current research approaches in screening soluble compounds for regenerative medicine, which are often based on one‐sample‐for‐one‐experiment principle.